A Case of Severe Acute Necrotizing Pancreatitis after Administration of Sitagliptin. Issue 6 (January 2013) - Sue, Mariko; Yoshihara, Aya; Kuboki, Koji; Hiroi, Naoki; Yoshino, Gen
A 55-year-old Japanese man with a 3-year history of type 2 diabetes mellitus was admitted to our hospital for upper abdominal pain. Control of diabetes mellitus was good with voglibose and metformin, with sitagliptin added to this regimen 8 months prior. His pancreatic enzyme levels were elevated, and abdominal computed tomography (CT) showed diffuse pancreatic swelling with fluid accumulation and ascites of CT grade 3. The patient was diagnosed with severe acute pancreatitis. There were no obvious causes for pancreatitis except the recently administered sitagliptin. Since incretin-related drugs entered the market, the number of incretin-related drugs prescriptions rapidly increased and so did the incidence of pancreatitis. There are several reports suggesting the correlation between incretin-related drugs and pancreatitis, such as a report based on data obtained from the United States Food and Drug Administration (FDA) which revealed a significant correlation between the administration of exenatide or sitagliptin and pancreatitis. However, there also is a report that denied the evidence for such in a large cohort study. The relation between incretin based drugs and pancreatitis is still controversial.